Modeling of cytochrome P450 (Cyt P450, CYP) channels. Issue 2 (2011) - Jankowski, Christopher K.; Chiasson, Julien B.; Dako, Étienne; Doucet, Kathy; Surette, Marc E.; André, Francois; Delaforge, Marcel
Abstract : The precise location of a substrate in cytochrome P450 (CYP) governs the orientation of the oxidation position. Such information is generally obtained from biochemical data, but modeling approaches have also been used to explain these locations. We used X-ray data and modeling techniques to distinguish between the series of putative linear or curved channels which lead the substrate from the outer side of the protein to the inner, and then into the heme pocket; these techniques were also used to identify the largest such channels. Two new methods for precisely determining the 3-D structure of proteins using X-ray crystallography were proposed in order to identify these channels: first, the use of both straight and curved channels, and second, the sphere method. These data are compared with Poulos channels, and with Caver (or Mol on line) modeling methodologies. Our methods were developed from studies of the interaction between cytochrome P450CAM (CYP101) from Pseudomonas putida (as expressed in Escherichia coli ) and the indolic base β-carboline. Apart from the identification of potential access channels leading to the heme-containing active site, a new explanation was advanced for the substrate's hydroxylation position. The sphere method seems to have potential to become a general and direct method for prediction of substrate access channels from reduced- or low-resolution crystallographic data.